A SiO2@MIP electrochemical sensor based on MWCNTs and AuNPs for highly sensitive and selective recognition and detection of dibutyl phthalate. (1st July 2022) - Wang, Shan; Pan, Mingfei; Liu, Kaixin; Xie, Xiaoqian; Yang, Jingying; Hong, Liping; Wang, Shuo
Highlights: Combining nanomaterials and surface molecular imprinting for sensor preparation. Taking carboxylation-modified SiO2 as the carrier to synthesize SMIPs. Controllable morphology, thin blotting layer and less encapsulation of SiO2 @MIP. Using MWCNTs and AuNPs to improve electrode sensitivity and electron transport. Simpler preparation, higher selectivity and lower cost of the SiO2 @MIP sensor. Abstract: A molecularly imprinted sensor for highly sensitive and selective determination of dibutyl phthalate (DBP) was fabricated by combining multi-walled carbon nanotubes (MWCNTs) and Au nanoparticles (AuNPs) with surface molecularly imprinted polymer (SMIPs). The MWCNTs and AuNPs were designed to modify the electrode surface to accelerate the electron transfer rate and enhance the chemical stability. SMIPs were synthesized using SiO2 microspheres as carriers. By loading SMIPs capable of identifying DBP on the surface of modified electrodes of MWCNTs and AuNPs, an electrochemical sensor for detecting DBP was successfully constructed. After optimizing the experimental conditions, the modified electrode SiO2 -COOH@MIP/AuNPs/MWCNTs/GCE can recognize DBP in the range of 10 −7 g L −1 to 10 −2 g L −1, and the detection limit achieved to 5.09 × 10 −9 g L −1 (S/N = 3). The results demonstrate that the proposed MIP electrochemical sensor may be a promising candidate electrochemical strategy for detecting DBP in complex samples.